A comprehensive investigation on electronic structure, optical and thermoelectric properties of the HfSSe Janus monolayer. (September 2020) - Hoat, D.M.; Naseri, Mosayeb; Hieu, Nguyen N.; Ponce-Pérez, R.; Rivas-Silva, J.F.; Vu, Tuan V.; Cocoletzi, Gregorio H.
Abstract: Electronic structure, optical and thermoelectric properties of the HfSSe Janus monolayer have been comprehensively investigated using first-principles calculations based on the full-potential linearized augmented plane-wave (FP-LAPW) method. Results show that the HfSSe Janus monolayer is dynamically stable. Electronic properties features indicate that the two-dimensional (2D) material at hand is an indirect gap semiconductor with a band gap of 0.756 eV calculated by the Wu-Cohen scheme within generalized gradient approximation (GGA-WC). The spin-orbit coupling (SOC) inclusion in the calculations breaks the degeneracy in both valence and conduction bands, and gives a smaller band gap of 0.653 eV. Additionally, the external strain effect on the electronic structure is also examined. The metallization can be achieved when a compressive strain of −8% is applied. Optical properties results suggest that the studied 2D monolayer may be a promising candidate to be applied in nano-optoelectronic devices provided that it displays a wide absorption band from visible to ultraviolet with high absorption coefficient of the order of 10 3 /cm. Finally, the thermoelectric properties including electrical conductivity, Seebeck coefficient, electronic thermal conductivity and power factor are calculated using the semi-classical Boltzmann transport theory. Results indicate that the electron doping may be favorable for the thermoelectric performance of the HfSSe Janus monolayer due to large power factor values as compared with those of the hole doping. Highlights: HfSSe monolayer is dynamically stable. HfSSe is an indirect gap semiconductor with a band gap of 0.756 eV. Spin-orbit coupling removes the energy degeneracy and decreases slightly the band gap. HfSSe shows good optical absorption from visible to ultraviolet regime. HfSSe possesses high thermopower and power factor, and the hole doping is favorable.